2022
DOI: 10.1002/ange.202204256
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Abstraction of Hydrogen Atoms from Water Using Hydroxylated Graphitic Carbon Nitride for Hydrogenative Coupling Reactions

Abstract: Employing pure water, the ultimate green source of hydrogen donor to initiate chemical reactions that involve a hydrogen atom transfer (HAT) step is fascinating but challenging due to its large HÀ O bond dissociation energy (BDE H-O = 5.1 eV). Many approaches have been explored to stimulate water for hydrogenative reactions, but the efficiency and productivity still require significant enhancement. Here, we show that the surface hydroxylated graphitic carbon nitride (gCNÀ OH) only requires 2.25 eV to activate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The vibrational bands at ca. 1160 cm –1 for tsCN- x originate from the presence of C–O bonds . With increasing the amount of glucose, the stretching mode of C–N undergoes an apparent redshift from 1233 to 1250 cm –1 (Figure c).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The vibrational bands at ca. 1160 cm –1 for tsCN- x originate from the presence of C–O bonds . With increasing the amount of glucose, the stretching mode of C–N undergoes an apparent redshift from 1233 to 1250 cm –1 (Figure c).…”
Section: Resultsmentioning
confidence: 94%
“…The XPS spectra of the C 1s orbital can be divided into three peaks centered at 284.8, 286.5, and 288.4 eV, belonging to C–C, C-NH x /C–O, and NC–N, respectively. , With increasing the content of glucose, the peak area ratios of C–C to NC–N and C-NH x /C–O to NC–N increase gradually (Figure d), suggesting that hydroxyls are formed and nitrogen atoms in NC–N are displaced by carbon atoms. The XPS spectra of the N 1s orbital can be divided into three peaks at 398.6, 399.9, and 401.0 eV, corresponding to the C–NC, N–C 3 , and C-NH, respectively . The peak area ratios of C–NC to N­(C) 3 decrease from 5.0 for CN-bulk to 4.0 for tsCN-50 (Figure e), indicating that the proportion of C–NC bonds decreases.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…16,17 Due to these attractive properties, especially its easy operability, a great deal of research into CN has been reported for photocatalytic applications, such as water splitting, industrial chemical synthesis, environment protection, etc. 18,19 However, the unmodified CN has low polymerization and low crystallinity, along with sluggish photogenerated electron and hole dynamics. Effective methods to overcome these drawbacks have been realized by regulating the electronic structure of carbon nitride by methods such as copolymerization with small organic molecules and assembly with other semiconductors to construct heterojunction or D-A systems.…”
Section: Introductionmentioning
confidence: 99%